Flexible Metal–Organic Frameworks as CO2 Adsorbents en Route to Energy‐Efficient Carbon Capture. Issue 5 (20th February 2022) - Yao, Xuan; Cordova, Kyle E.; Zhang, Yue-Biao
Abstract : Innovation in the realm of adsorbents for carbon capture is a necessity for meeting the carbon neutrality goal by 2060. Flexible metal–organic frameworks (MOFs) hold great promise for energy‐efficient carbon capture as a direct result of their high working capacity, high selectivity, and intrinsic thermal management during gate‐opening adsorption. In this review, the development and recent progress of flexible MOFs are summarized, the reported methods for control over flexibility are outlined, and the challenges and potential solutions of these materials toward practical carbon capture are discussed. It is envisioned that a deep molecular understanding of the adsorption mechanism in conjunction with a handle over gate‐opening phenomena is a critical element for promoting the performance and large‐scale application of flexible MOFs. Abstract : Metal–organic frameworks (MOFs) have shown great potential in carbon capture with high performance and high energy efficiency. However, there is a tripartite trade‐off among adsorption selectivity, working capacity, and regeneration energy. Flexible MOFs, featuring the CO2 adsorption‐induced structural transformation, represent an exclusive opportunity with high selectivity, high capacity, and intrinsic thermal management en route to energy‐efficient carbon capture.